2015
DOI: 10.1017/s003329171500272x
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of eating disorders in Dutch primary care: decreasing incidence of bulimia nervosa but not of anorexia nervosa

Abstract: The incidence rate of BN decreased significantly over the past three decades, while the overall incidence rate of AN remained stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 42 publications
10
58
1
4
Order By: Relevance
“…Amenorrhea was removed as a criterion due to a recognition that endocrine dysregulation in anorexia nervosa is variable, and that some women with low weight and all the psychiatric features of anorexia nervosa continue to have regular menses 2 . Before these revisions, the incidence of anorexia nervosa in Europe had been stable since the 1970s according to primary care-based records 3,4 . However, the incidence seemed to be increasing among adolescent and young women aged 10–24 years according to a primary care-based study in the Netherlands and a population-based study in Rochester, Minnesota, USA 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amenorrhea was removed as a criterion due to a recognition that endocrine dysregulation in anorexia nervosa is variable, and that some women with low weight and all the psychiatric features of anorexia nervosa continue to have regular menses 2 . Before these revisions, the incidence of anorexia nervosa in Europe had been stable since the 1970s according to primary care-based records 3,4 . However, the incidence seemed to be increasing among adolescent and young women aged 10–24 years according to a primary care-based study in the Netherlands and a population-based study in Rochester, Minnesota, USA 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Before these revisions, the incidence of anorexia nervosa in Europe had been stable since the 1970s according to primary care-based records 3,4 . However, the incidence seemed to be increasing among adolescent and young women aged 10–24 years according to a primary care-based study in the Netherlands and a population-based study in Rochester, Minnesota, USA 4,5 . Since the advent of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (known as DSM-5) and broadening of the diagnostic criteria for anorexia nervosa, investigators have seen a substantial increase in the prevalence of anorexia nervosa 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Whether the incidence of eating disorders (EDs) has changed over time has been a subject of debate (Smink et al, ). Earlier case register studies showed that the incidence of anorexia nervosa (AN) increased before the 1970s (Hoek, ; Keel & Klump, ), whereupon it seemed to stabilize throughout the 2000s (Currin, Schmidt, Treasure, & Jick, ; Smink et al, ; Steinhausen & Jensen, ; Van Son, Van Hoeken, Bartelds, Van Furth, & Hoek, ) and 2010s (Currin et al, ; Keel & Klump, ; Reas & Ro, ; Steinhausen & Jensen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family, friends, social view, and feelings body parts imbalance affected body image satisfaction. Smink et al (2016) investigated bulimia nervosa and its correlation with anorexia nervosa. The purpose was to study changes in eating disorder occurrence in Netherlands during 1985-1989, 1995-1999, and 2005-2009.…”
Section: Introductionmentioning
confidence: 99%